Paris 2024: Evaluation of the elite sport expenditure and success of 17 nations - De Bosscher, V.; Shibli, S.; Smismans, S.; Weber, A. C.; Abigael, L.; Botwina, G.; Brosnan, G.; Codoni, D.; Coeckelberghs, T.; Courtin, O.; Descheemaeker, K.; Ferkins, L.; et al. (Owl Press, 2024)
In the run-up to the Paris 2024 Olympic and Paralympic Games, the SPLISS consortium invited nations with an interest in elite sport development systems to (voluntarily) take part in an exercise to quantify their nationally coordinated expenditure on elite sport. In total, 17 nations accepted the challenge and participated in a benchmark study called SPLISS Pillar 1 - Light 2024. This report aims to evaluate the financial support for elite sport and to analyse the success achieved at the Paris 2024 Olympic Games. Funding is the first Pillar of the nine Pillar SPLISS model and quantifies the most important input to the process of producing elite athletes capable of competing at the highest level of international sport. The objective for each nation is to be efficient with their financial budgets, striving to achieve optimal performance (i.e. outputs) with minimal support. This is an indicator of the efficiency of elite sport investments and the effectiveness of policies. The processes that show how funding is invested and how elite sport policy is developed in each nation, are not measured in this SPLISS Pillar 1 - Light 2024 study. This is reflected by Pillars 2-9, which are indicators of the throughput stage. Finally, as ever more nations strive for Olympic success by investing strategically in elite sport, resulting in increasing government funding globally, there has been a clear shift in discourse amongst these governments from winning Olympic medals to delivering societal outcomes or impact such as togetherness, national pride and identity, wellbeing, and boosting grassroots sport participation.